EFL TEACHERS’ PROBLEMS IN ONLINE LEARNING DURING COVID-19 PANDEMIC AND THEIR SOLUTION - Markhamah Amah; Zuhiriyah, Mukminatus (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The spread of COVID-19 in Indonesia has had a major impact on the education sector, requiring schools to close and change the learning system, which becomes an online learning system. The purpose of this study was to find out the problems by English junior high school teachers and their solutions. The researcher used descriptive qualitative method. The research subject were six English teachers from two English teachers in MTs Salafiyah Syafi’iyah Tebuireng, MTsN 9 Jombang, and SMPN 2 Diwek. The researcher used data collection techniques with interview guidlines. The results from this study describe that English teachers faced several problems in the online teaching process, especially in teaching reading, and speaking. The problem was due to the absence of direct interaction between the English teacher and students and students still had difficulty reading English texts, the absence of direct interaction between the English teacher and students, the lack of motivation of students, the difficulty of students in accessing online learning, having an electronic device, and the lack of parental guidance of students. As an educator, the English teacher provides solutions to the problems mentioned above in order to anticipate the course of online learning. The solutions for online learning problems due to providing material and assignments using learning applications, and include providing learning materials, preparing online teaching, approaching students, and communicating with parents of students. Hopefully, this study can provide benefits from the results of the problems faced by English junior high school teachers and their solutions in online teaching. So, they can improve their ability in teaching English lessons.